A comparative study of term creation processes in Isixhosa and Isizulu translations of the South African Constitution - Sineke, Thembela Gloria (My University, 2006)
The study deals with term creation in translation comparing isiXhosa and isiZulu in relation to paraphrasing, borrowing, compounding, semantic transfer and derivation as five major processes used by translators in African Languages to compensate for terminology gap. The study is conducted within the Descriptive Translation Studies approach and it deals with how translator’s strategies are influenced by norms. The extracted source text terms in this study are from the English Constitution as the source text whilst the isiXhosa and isiZulu terms are extracted from the isiXhosa and isiZulu Constitutions respectively. The study has indicated that out of the five selected processes, paraphrasing is the most frequently chosen strategy in African Languages. With regard to borrowing, it has been shown that not all types of borrowing (as discussed by Cluver 1989) are possible in these languages and that every borrowed term has to be modified according to phonological, morphological and orthographical rules of these two languages. The study is concluded by arguing that term creation processes in translation are universal features of translated texts in African languages and they are effective translation strategies in languages of limited diffusion. In addition, translated texts are sources/ depositories of terminology and consequently they can play a role in language development activities.
MASTERS FACULTY OF HUMANITIES SCHOOL OF LITERATURE AND LANGUAGE STUDIES STUDENT NO: 0111542N
Keywords: paraphrasing; isiXhosa; borrowing; isiZulu; compounding; African Languages; semantic transfer; terminology gap; derivation; constitution